2017
DOI: 10.1200/jop.2017.022566
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physician Orders for Life-Sustaining Treatment Form Use With End-of-Life Care Quality Metrics in Patients With Cancer

Abstract: Advance care planning with completion of POLST forms compared with ADs in patients with advanced cancer was associated with two quality end-of-life care metrics: OHD and hospice admission. Our study suggests that goals-of-care discussions including POLST form completion may improve end-of-life care for patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…Cancer types included breast, 42 hematological, 35,33 gynecological, 1,34,48 lung or gastrointestinal, 39 and any type. 23,31,32,[36][37][38]40,41,43,45,46,48,51 Sample sizes ranged from 84 to 2752 participants, with a median of 226 participants per study. Two studies featured fewer than 100 participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer types included breast, 42 hematological, 35,33 gynecological, 1,34,48 lung or gastrointestinal, 39 and any type. 23,31,32,[36][37][38]40,41,43,45,46,48,51 Sample sizes ranged from 84 to 2752 participants, with a median of 226 participants per study. Two studies featured fewer than 100 participants.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Eighteen studies assessed relationships between EOL discussions and health-care utilization near death 1,23,[32][33][34][35][38][39][40][41][42][43][45][46][47][48]51 and 6 studies assessed place of death. 1,33,35,42,47,51 In addition, 6 studies incorporated elements of time in their assessment of EOL discussions, generally referring to these discussions as early (31þ days before death) or late (within 30 days of death), with later conversations typically occurring in inpatient settings. 1,23,31,41,48…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 A recent study showed that compared with standard advance directives, POLST completion increased out-of-hospital deaths and was associated with a greater likelihood of hospice admission in patients with advanced cancer. 12 Regardless of whether patients elect to document their preferences via living wills, POLST forms, or through designation of a health care proxy, ACP is a powerful component of oncologic care that honors the humanness of patients living with and dying from cancer.…”
Section: Acp: History Impact and Documentationmentioning
confidence: 99%
“…Our findings beg the question of what may be done to temper the use of nonbeneficial and expensive healthcare services among patients with exceedingly high morbidity and short life expectancy. Although we did not find that advance care planning or palliative care consultation independently impacted EOL healthcare intensity, others have demonstrated a multitude of benefits associated with palliative care consultation and advance care planning both near the EOL and concurrent with disease-directed treatment in both solid tumor and hematologic malignancy patients [18,20,[33][34][35][36][37][38][39][40]. Various models have been proposed for integrating palliative care into the bone marrow transplant setting, particularly in pediatric populations [41].…”
Section: Discussionmentioning
confidence: 99%